BALTIJOS ŠALIŲ FILOSOFINIO DISKURSO POSOVIETINĖ TRANSFORMACIJA I. - Kabelka, Gintaras (Problems / Problemos, 2013)
The paper presents a comparative analysis of philosophical discourses (1955-2011) and their post-soviet changes in three Baltic countries -- Estonia, Latvia, and Lithuania. Special attention is paid to the scope, growth rate, productivity and structural changes of these discourses. In the first part of this paper a general overview of philosophy in Latvia and Estonia is introduced to the Lithuanian readers. The main philosophical trends and problems are discussed, as well as particularity of each country. The paper surveys the history of philosophical centres, the formation of philosophical groups and disputes, and the ties among the discourses. The more characteristic tendencies in professional biographies of philosophers are explained and compared.